2009
DOI: 10.1177/0218492309103309
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis and Outcomes of Sleeve Resection versus Pneumonectomy

Abstract: To compare the outcome of sleeve resection or complex sleeve resection versus (Vs) pneumonectomy for lung cancer in a single unit. Between 1998 and 2006, 664 lung resections were carried out. There were 129 (19.4%) pneumonectomies and 79 (11.9%) sleeve resections; Twenty one patients (26.5%) underwent a complex sleeve resection. Operative mortality for the sleeve resections (SR) was 2.5% and for the pneumonectomies 8.53%. Overall 5-year survival after SR was 46.8% and after pneumonectomy 37.1%. The survival cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
19
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
5
19
2
1
Order By: Relevance
“…Similar results were achieved for differences in survival at 3 years (in six studies [9,10,15,17,18,23], RD 0.15, 95% CI 0.06, 0.24) and 5 years (in twelve studies [9-11,13-18,21-23], RD 0.15, 95% CI 0.09, 0.20). All the estimated combined RD were statistically significant.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were achieved for differences in survival at 3 years (in six studies [9,10,15,17,18,23], RD 0.15, 95% CI 0.06, 0.24) and 5 years (in twelve studies [9-11,13-18,21-23], RD 0.15, 95% CI 0.09, 0.20). All the estimated combined RD were statistically significant.…”
Section: Resultssupporting
confidence: 78%
“…Locoregional recurrences were reported in ten studies [8,10,13-15,18,21,23-25] and resultant data from meta-analysis showed the pooled locoregional recurrence in sleeve lobectomy was 14.44% (104/720) compared with 26.08% (451/1,729) in pneumonectomy, but this was not statistical significant (OR 0.78, 95% CI 0.47, 1.29), as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the last 2 decades many authors have reported the positive results and the efficacy of the bronchial sleeve resection [5][6][7][8]. PA resection and reconstruction do not seem to be a real alternative to pneumonectomy because of the discouraging results in complications [9].…”
mentioning
confidence: 99%
“…Postoperative morbidity and mortality data reveal overall better results for patients undergoing SL with respect to PN (15,18,31,32) (Table 2). These results justify the increasing use of parenchymal sparing procedures for lung cancer also in patients with good cardio-pulmonary function, as observed in the last years.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Moreover, in the analysis of 5-year survival according to stage and nodal status, SL results in higher survival rates for stages I, II. The survival advantage in stage III patients appears to be limited (17,25,31) (Table 1). In a report by Ludwig (6), sleeve lobectomy results in a more favourable prognosis with a survival advantage in patients with N0, N1 and N2 disease.…”
Section: Analysis Of Resultsmentioning
confidence: 99%